Transmission dynamics and epidemiology of dengue: insights from age-stratified sero-prevalence surveys - Ferguson,NM; Donnelly,CA; Anderson,RM (Philos Trans R Soc Lond B Biol Sci, 1999)
The relationship between infection with the four major serotypes of dengue virus and the occurrence of different forms of disease is complex and not fully understood. Interpreting longitudinal records of the incidence of serious disease to gain insight into the transmission dynamics and epidemiology of the virus is therefore complicated. Since age reflects duration of exposure, age-stratified, strain-specific serological surveys carried out at one point in time, or over a short time interval, can potentially provide a rich source of information on longitudinal patterns. This paper describes the development and application (to data collected in Thailand) of statistically rigorous methods designed to estimate time-varying, strain-specific forces of infection, and thus basic reproduction numbers, from cross-sectional serological data. The analyses provide support for the hypothesis that antibody-dependent enhancement of transmission influences observed epidemiological pattern. Age-stratified serological data also reveal evidence of a propensity for the annual incidence of infection to oscillate over time with a frequency of several years. The latter observation is consistent with the predictions of simple mathematical models of the transmission dynamics of the virus. The estimates of the basic reproduction numbers obtained are similar in magnitude for each dengue serotype, being in the range of four to six. Such values are higher than those obtained from earlier analyses, and the implications of this for dengue control are discussed.